1997
DOI: 10.1007/bf01301431
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and incidence of degenerative spine changes in patients with a lumbo-sacral transitional vertebra

Abstract: The purpose of this prospective study was to determine the overall incidence and distribution of lumbo-sacral degenerative changes (i.e. disc protrusion or extrusion, facet degeneration, disc degeneration, nerve root canal stenosis and spinal stenosis) in patients with and without a lumbo-sacral transitional vertebra (LSTV). The study population consisted of 350 sequential patients with low back pain and/or sciatica, referred for medical imaging. In all cases CT scans of the lumbosacral region were obtained. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
0
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(97 citation statements)
references
References 11 publications
2
91
0
4
Order By: Relevance
“…In a previous study, Elster [4] demonstrated that central and lateral spinal stenosis is much more common at or near the interspace above the transitional vertebra. In contrast, a recent study conducted by Vergauwen et al [18], in which they measured the spinal canal diameters in adult patients with LBP and with or without LSTV on computed tomographic (CT) scan, found no significant difference in the distribution of spinal stenosis between the two groups.…”
Section: Hasan Oguz Selami Akkuş Serdar Tarhan Saim Açikgözoglu Memdumentioning
confidence: 82%
See 4 more Smart Citations
“…In a previous study, Elster [4] demonstrated that central and lateral spinal stenosis is much more common at or near the interspace above the transitional vertebra. In contrast, a recent study conducted by Vergauwen et al [18], in which they measured the spinal canal diameters in adult patients with LBP and with or without LSTV on computed tomographic (CT) scan, found no significant difference in the distribution of spinal stenosis between the two groups.…”
Section: Hasan Oguz Selami Akkuş Serdar Tarhan Saim Açikgözoglu Memdumentioning
confidence: 82%
“…However, the role of these radiographic abnormalities in the etiology of LBP is unclear [1,3,4,15,18,19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations